Correction: Expression of genes with biomarker potential identified in skin from DSLD-affected horses increases with age. - Jennifer Hope Roberts; Jian Zhang; Florent David; Amy McLean; Karen Blumenshine; Eva Müller-Alander; Jaroslava Halper (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0287740.].